2013
DOI: 10.3390/nu5010267
|View full text |Cite
|
Sign up to set email alerts
|

A National Observational Study of the Prevalence and Use of Enteral Tube Feeding, Parenteral Nutrition and Intravenous Glucose in Cancer Patients Enrolled in Specialized Palliative Care

Abstract: The use of artificial nutrition remains controversial for cancer patients in palliative care, and its prevalence is largely unknown. We therefore conducted a national study to investigate the prevalence, indications for, and perceived benefit of enteral/parenteral nutrition and intravenous glucose in this patient group. A cross-sectional study was performed within the palliative care research network in Sweden (PANIS), using a web-based survey with 24 questions on demographics, prescribed nutritional treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
2
23
1
5
Order By: Relevance
“…One study, conducted in an inpatient palliative care unit, revealed that 1.8% of patients received PN during their stay in the unit 29 . However, some data suggest that PN use in palliative care may be more common than previously thought, with some variation across counties 20 , 30 . One systematic review with meta‐analysis of home PN in patients with inoperable MBO involved 437 patients, one of the largest cohorts to date 20 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
“…One study, conducted in an inpatient palliative care unit, revealed that 1.8% of patients received PN during their stay in the unit 29 . However, some data suggest that PN use in palliative care may be more common than previously thought, with some variation across counties 20 , 30 . One systematic review with meta‐analysis of home PN in patients with inoperable MBO involved 437 patients, one of the largest cohorts to date 20 .…”
Section: Question 9: Is Pn Appropriate For Patients In Palliative Care?mentioning
confidence: 99%
“…In a Swedish observational study of the prevalence and use of artificial nutrition in palliative patients, 22% of inpatients and 11% of those in home care services received artificial nutrition, with PN being most common [69].…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…Malnutrition is highly prevalent in patients with disease states such as cancer, cerebrovascular accidents, or other neurologic disorders (amyotrophic lateral sclerosis), resulting in significant complications and high mortality. [1][2][3][4][5] Early nutrition intervention has been shown to significantly improve outcomes, [6][7][8] which has caused an increase in the use of acute inpatient and long-term home enteral nutrition (HEN) over the last few decades. [9][10][11][12][13] Despite the benefits, HEN can be associated with significant complications with the enteral tube itself (tube site infection, granulation tissue formation, leaking around insertion site, etc) or difficulties with provision of enteral formula.…”
mentioning
confidence: 99%